2012
DOI: 10.1097/ico.0b013e31823f8bcc
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Presumed Iatrogenic Graft Failure in Descemet Stripping Automated Endothelial Keratoplasty

Abstract: Overall, DSAEK failure rates improve as surgeons gain experience. Failure rates in cornea fellowship programs are not excessive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Other studies have also revealed that primary failures occur more frequently during the learning curve. 15 One failure was associated with implantation of a femtosecond laser cut donor graft. Visually compromising interface haze seems to be a significant limitation for the use of femtosecond lasers in posterior lamellar donor preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also revealed that primary failures occur more frequently during the learning curve. 15 One failure was associated with implantation of a femtosecond laser cut donor graft. Visually compromising interface haze seems to be a significant limitation for the use of femtosecond lasers in posterior lamellar donor preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, graft failures were observed in 10% of patients with FED during the first 4 years, whereas graft failures occurred in 7% of the patients in this study. A possible explanation may be an improvement in the graft failure rate along with the surgeons' experience (Mojica et al 2012). Both studies were performed at Aarhus University Hospital, Denmark, by the same surgeons, but initially DSAEK surgery was performed mainly on patients with Fuchs endothelial dystrophy rather than in patients with secondary endothelial failure.…”
Section: Discussionmentioning
confidence: 99%
“…13 Price et al 11 also emphasized that graft survival seems more likely in hospitals which perform a higher number of interventions. One study which analyzed iatrogenic failure in DSAEK 27 pointed out that failure rates improved together with surgeon experience, with a mean percentage of 21.8% of failures with surgeons having little experience (1-10 interventions), against 1.5% in the group with more experience (>100 interventions).…”
Section: Safetymentioning
confidence: 97%